The Erosion of the Middle Class – Threat to the Development of the Welfare State - E. A. Maryganova (Управление)
The article deals with the problems and consequences of inequality in society and the erosion of the middle class in the developed countries, as well as the particularities of these processes in Russia. The result of the growing inequality in the United States and other leading countries is an aggravation of social problems. It is difficult for a large number of young people to get а high-quality education and, in the long run, paid jobs and their own homes. There has been a deterioration of health, reduction of life expectancy for the poorest sectors of the population, increase in crime and in the number of people in custody. Leading scientists from the West offer solutions to these problems. The article shows that Russian “middle class” has the essential features and is still in the course of its formation. Crisis of 2014 damaged Russian middle class, which performs important functions in the economic and social development of Russia. That class is the main consumer of the produced economic benefits; investor whose savings are channeled to the development of the economy. Representatives of the middle class generate and accumulate human capital needed for the development of an innovative economy. The crucial role of this layer of society is to serve as a social stabilizer. The slowdown of the middle class, and even more, its size reduction can cause serious damage to the economic and social development of Russia.